MARITIME SECURITY REGULATION CONCERNING INTERNATIONAL SHIP AND PORT FACILITY SECURITY CODE 2002 AND ITS IMPLEMENTATION IN INDONESIA - Ayu Kusuma Wardani (Faculty of Law Universitas Lampung, 2021)
Ministerial Regulation Number 134 of 2016 is a form of ratification of the International Ship and Port Facility Security Code 2002 (ISPS Code, 2002), the objective of which is to establish a consistent standard framework for evaluating risk and enabling the government to compensate for changes in threats through measures appropriate safety measures. In its development, there are several regulations related to implementing the 2002 ISPS Code in Indonesia. These regulations were formed by adjusting the standard regulations in the 2002 ISPS Code with the safety conditions of ships and ports in Indonesia. The problem is, Indonesia has several large ports that operate as international ports in international trade. The type of research used is normative legal research sourced from primary, secondary, and tertiary legal materials whose data collection is carried out by literature study. The results of the study show two things: (1) Maritime security arrangements relating to shipping safety standards and port facilities in the 2002 ISPS Code are divided into two parts, namely part A (Part A) containing systematic arrangements and implementation of the ISPS Code for signatory countries including and Definition, Purpose, Scope of Ship Safety Standards and Port facilities and ISPS Code Compliance Procedure. And part B (Part B) contains further explanation about part A including Determination of Security Level, Implementation of Ship Security, Implementation of Port Facility, and Information and Communication Security. (2) The implementation of the maritime security regulation related to security standards ships and port facilities in the ISPS Code in 2002 in Indonesia contained in via Law No. 17 the Year 2008 on the voyage, Ministerial Regulation Number 134 the Year 2016 concerning Management of Ship Safety and Port Facilities.